2008
DOI: 10.1270/jsbbs.58.121
|View full text |Cite
|
Sign up to set email alerts
|

Development of transgenic rice (Oryza sativa L.) expressing wheat high-and low-molecular-weight glutenin subunit proteins

Abstract: We isolated transformation-competent artificial chromosome (TAC) clones harboring a high-molecularweight glutenin subunit (HMW-GS) gene and a low-molecular-weight GS (LMW-GS) gene from wheat genomic DNA, and developed transgenic rice lines with these genes using a transformation system mediated by Agrobacterium tumefaciens. We developed two lines of transgenic rice, one expressing the gene coding for HMW-GS and the other expressing the gene coding for LMW-GS. By crossing these transgenic lines, a novel line ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Protein extraction and Western blot T1 generation seeds were frozen in liquid nitrogen and then ground to powder using a mortar and pestle. Total storage proteins in the rice endosperm were extracted with 50mM Tris-HCl (pH 8.0) containing 2% SDS, 50% of 1-propanol and 1% of dithiothreitol, as described [4]. Amount of extracted total proteins was measured by Nanodrop Spectrophotometer (ND-1000, Thermo Fischer Scientific, Wilmington DE, USA).…”
Section: Southern Hybridization Analysismentioning
confidence: 99%
“…Protein extraction and Western blot T1 generation seeds were frozen in liquid nitrogen and then ground to powder using a mortar and pestle. Total storage proteins in the rice endosperm were extracted with 50mM Tris-HCl (pH 8.0) containing 2% SDS, 50% of 1-propanol and 1% of dithiothreitol, as described [4]. Amount of extracted total proteins was measured by Nanodrop Spectrophotometer (ND-1000, Thermo Fischer Scientific, Wilmington DE, USA).…”
Section: Southern Hybridization Analysismentioning
confidence: 99%
“…Total storage proteins in the rice endosperm were extracted with 50mM Tris-HCl (pH 8.0) containing 2% of SDS, 50% of 1-propanol and 1% of dithiothreitol, as described by Araki et al 2008. Proteins were precipitated in cold 80% acetone.…”
Section: Expression Of Glu-1dx5 In Transgenic Rice Endospermmentioning
confidence: 99%
“…The protein detected in our transgenic T 2 endosperm was similar in size to the wheat Glu-1Dx5 product detected in transformed maize plants (Sangtong, 2002). Araki et al (2008) suggested that the protein-processing system was conserved in both rice and wheat, and that it was possible to produce wheat glutenin using the proteinprocessing system of rice. The gene we transferred to rice was slightly different from that reported by Araki et al (2008), since we used 8.2 kb of the genomic DNA of Glu-1Dx5 that includes the native promoter of the Glu1Dx5 gene.…”
Section: Expression Of Glu-1dx5 In Transgenic Rice Endospermmentioning
confidence: 99%
See 2 more Smart Citations